KETERLIBATAN KARYAWAN DAN PERILAKU INOVATIF: SEBUAH TINJAUAN LITERATUR - Fatwa Zuhaena; Harsuti Harsuti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
This study aims to: a) provide a comprehensive understanding of the relationship between employee interactions and innovative behaviour, and b) build an integrative conceptual framework based on validated factors empirically and that relationship with relevant theories. An integrative literature review from empirical studies shows that employees perceive the combination of high demand and high resources to be ideal interaction. Innovative behaviour is a consequence of these complex interaction. Engaged employees tend to more innovative by coping strategy activities to face the challenge.